Investigations on the unique design of heat pipe-assisted thermal management system with novel Chaudhari-Padalkar-Funde number and heat transfer correlations - Akshay B. Padalkar; Mangesh B. Chaudhari; Adinath M. Funde (Results in Engineering)
The demand for a clean energy storage source in the automobile industry is being fulfilled effectively by the use of electric vehicles (EVs). The most prominent battery technology commercially preferred in EVs is lithium-ion batteries. However, the enormous amount of heat generated while cycling the batteries hinders the overall performance, life cycle, and safety. Therefore, controlling the temperature rise of batteries below the acceptable ranges is vital. Several thermal management techniques are available, but Heat Pipes (HPs) are one of the most efficient and promising technologies. The incorporation of HP in batteries is a difficult task for effective heat extraction. The novelty of the current work lies in the incorporation of HP at central cavities in a cylindrical cell battery, which utilizes the circumferential surface area with the aid of a battery cell contactor. The vertical HP extracts the heat and dissipates it through the top fins. The new non-dimensional number is proposed, named the CPF number (Chaudhari-Padalkar-Funde number) and the heat transfer correlation is developed for the current HP design. The CPF number describes the rate of heat generation to rate of heat dissipation. The physical significance of CPF number reveals the effectiveness of designed TMS. The experimental results reveal that HP with forced convection drops the temperature rise to 51.7 °C with an airflow velocity of 2 ms-1 and up to 47.8 °C with an airflow velocity of 4 ms-1 at a 3C discharge rate. The simulation results of temperature distribution reveal that the peak temperature difference (∆Tmax) within the battery pack is also maintained below 3 °C. Although the mass of the system increased by 18.2 %, the effectiveness of heat extraction increased by 63.5 %. The performance, as analysed by the trade-off score, is 3.32, indicating a highly efficient designed system. The proposed design of a subgroup of 2s2p battery packs is easily replicable to larger-sized cylindrical cell battery packs for EV applications.